Dietary assessment of ochratoxin A in Chinese dark tea and inhibitory effects of tea polyphenols on ochratoxigenic Aspergillus niger - Zhao, Yi-qiao; Jia, Wen-bao; Liao, Si-yu; Xiang, Lin; Chen, Wei; Zou, Yao; Zhu, Ming-Zhi; Xu, Wei (Frontiers in Microbiology, 2022)
In recent years, there has been an increasingly heated debate on whether Chinese dark tea is contaminated with mycotoxins and whether it poses health risks to consumers. In this study, a rapid method based on high-performance liquid chromatography was used to detect ochratoxin A (OTA) in Chinese dark tea samples from different regions of China and different years. Of the 228 Chinese dark tea samples tested, 21 were detected for OTA contamination, with a concentration ranging from 2.51±0.16 to 12.62±0.72 μg/kg. Subsequently, a dark tea drinking risk assessment was conducted, and the hazard quotient for each group was far below the acceptable level of 1.0. Of the 12 Aspergillus spp. strains isolated, one strain of Aspergillus niger had the ability to produce OTA. We also found that tea polyphenols and epigallocatechin gallate inhibited the growth of ochratoxin-producing Aspergillus niger and the expression of non-ribosomal peptide synthetase (NRPS), a key gene for ochratoxin synthesis. Thus, OTA contamination of dark tea is at an acceptable risk level, and the inhibition of ochratoxigenic Aspergillus niger by polyphenols provides new insights into the detoxification of ochratoxins and the safety of dark tea consumption.